2021
DOI: 10.1111/pbi.13596
|View full text |Cite
|
Sign up to set email alerts
|

VvHDZ28 positively regulate salicylic acid biosynthesis during seed abortion in Thompson Seedless

Abstract: Summary Seedlessness in grapes is one of the features most appreciated by consumers. However, the mechanisms underlying seedlessness in grapes remain obscure. Here, we observe small globular embryos and globular embryos in Pinot Noir and Thompson Seedless from 20 to 30 days after flowering (DAF). From 40 to 50 DAF, we observe torpedo embryos and cotyledon embryos in Pinot Noir but aborted embryos and endosperm in Thompson Seedless. Thus, RNA‐Seq analyses of seeds at these stages from Thompson Seedless and Pino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 106 publications
(115 reference statements)
0
21
0
Order By: Relevance
“…Besides, boron deficiency can affect pollen germination, pollen tube growth, fruit set, and seed formation, thereby inhibiting reproductive growth ( Alva et al, 2015 ). Previous studies on seedless phenotype were principally focused on other species, such as Arabidopsis ( Goetz et al, 2007 ), tomato ( Klap et al, 2017 ; Takisawa et al, 2018 ; Molesini et al, 2020 ), grapevine ( Malabarba et al, 2017 ; di Rienzo et al, 2021 ; Li et al, 2021 ), citrus ( Zhang et al, 2018 ; Liang et al, 2020 ), eggplant ( Chen et al, 2017 ), sugar apple ( Lora et al, 2011 ), and pear ( Wang et al, 2021a , b ).…”
Section: Introductionmentioning
confidence: 99%
“…Besides, boron deficiency can affect pollen germination, pollen tube growth, fruit set, and seed formation, thereby inhibiting reproductive growth ( Alva et al, 2015 ). Previous studies on seedless phenotype were principally focused on other species, such as Arabidopsis ( Goetz et al, 2007 ), tomato ( Klap et al, 2017 ; Takisawa et al, 2018 ; Molesini et al, 2020 ), grapevine ( Malabarba et al, 2017 ; di Rienzo et al, 2021 ; Li et al, 2021 ), citrus ( Zhang et al, 2018 ; Liang et al, 2020 ), eggplant ( Chen et al, 2017 ), sugar apple ( Lora et al, 2011 ), and pear ( Wang et al, 2021a , b ).…”
Section: Introductionmentioning
confidence: 99%
“…The nucleotide-binding domain and leucine-rich repeat containing protein NBS-LRR is the major plant immune receptor family (Calvo-Baltanás et al 2021). The NBS-LRRs work upstream of the SA pathway, and the key defense response factor NPR1, which belongs to the NBS-LRR family, could be activated in the stress response to promote cell death via SA signaling and induce seed abortion (Bomblies and Weigel 2007;Li et al 2021). Both NPR1 and SID2 were known to promote cell death in the SA pathway, when NPR1 or SID2 was inhibited, and due to a negative effect the number of viable seeds was increased (Burkart-Waco et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Levels of endogenous salicylic acid (SA) were much higher in the seedless 'Crimson Seedless' and in the seeded 'Red Globe' after 4 weeks of flowering, indicating an autoimmune defense response (Royo et al 2018) and a SA-dependent immune defense response in seed abortion (Burkart-Waco et al 2013). More recent research showed that seed abortion was a programmed cell death (PCD) process, whereby the high SA content induced the expression of a positive regulator(s) of SA synthesis and enhanced the expression of downstream related PCD genes (Li et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Comparative transcriptomics and genomics of conifer developmental studies are currently being used for these purposes [10], and a database of research related to the study of conifer genera and species [1,2] will be useful for further studies on a more comprehensive and solid basis. These aspects are not unique to conifer studies, and they also have great importance in other fields [11]. However, in conifers, which have such a varied global distribution in disparate environments, and which maintain enormous adaptability and diversification, the challenge is even greater.…”
Section: General Traits Distribution and Diversitymentioning
confidence: 99%